Pengembangan Media Dakwah Kontemporer Berbasis Website: Studi Kasus pada WWW. Assajidin. Com - Anang Walian (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2019)
This study uses the theory of Diffusion of Innovation in the discipline of Communication Sciences whose basic assumption is how to spread an innovation to other parties. This study uses qualitative data with data collection techniques through: interviews, observation, and documentation. The data were analyzed interactively by the Miles and Huberman models: Data Reduction, Data Display, and Verification Conclusion. The results of the study indicate that this website was established to carry out Islamic da'wah and also efforts to deal with secularistic thoughts. Some of the efforts that can be made to advance this website are: participating in information technology exhibition, expanding networking with other agencies, expanding criminal report, increasing advertising, product integration, expanding social media networks, and expanding rubric. Then the obstacles faced were the lack of HR in the IT field, the lack of advertising, the small number of contributors to articles by academics, new experiences, and the lack of special journalists on the website. However, there are several factors that support the advancement of this website are: the increasing number of internet users every day, the amount of public interest in da'wah through the website, and the existence of Assajidin Tv which can complement its audio visual coverage.